SPECIAL METHODOLOGY IN TEACHING PHONETICS TO YOUNG LEARNERS - Yuldashev Og‘abek Komiljon o‘g‘li; Mohinur Gʻofurjonova (Ustozlar uchun, 2025)
Abstract: Teaching phonetics to young learners requires unique and effective methodologies tailored to their cognitive development and learning styles. This course paper explores practical and creative approaches for teaching English phonetics to children aged 6 to 12. It highlights the importance of early phonetic instruction, introduces interactive tools such as songs, chants, games, and visual materials, and emphasizes the role of fun and repetition. The purpose of the paper is to equip teachers with strategies that enhance pronunciation, listening, and speaking skills in young learners, while fostering motivation and language confidence.